Plant extract‐based synthesis of metallic nanomaterials, their applications, and safety concerns. Issue 9 (9th June 2022) - Ullah, Aziz; Lim, Sung In
Abstract: Nanotechnology has attracted the attention of researchers from different scientific fields because of the escalated properties of nanomaterials (NMs) compared with the properties of macromolecules. NMs can be prepared through different approaches involving physical and chemical methods. The development of NMs through plant‐based green chemistry approaches is more advantageous than other methods from the perspectives of environmental safety, animal, and human health. The biomolecules and metabolites of plants act as reducing and capping agents for the synthesis of metallic green NMs. Plant‐based synthesis is a preferred approach as it is not only cost‐effective, easy, safe, clean, and eco‐friendly but also provides pure NMs in high yield. Since NMs have antimicrobial and antioxidant potential, green NMs synthesized from plants can be used for a variety of biomedical and environmental remediation applications. Past studies have focused mainly on the overall biogenic synthesis of individual or combinations of metallic NMs and their oxides from different biological sources, including microorganisms and biomolecules. Moreover, from the viewpoint of biomedical applications, the literature is mainly focusing on synthetic NMs. Herein, we discuss the extraction of green molecules and recent developments in the synthesis of different plant‐based metallic NMs, including silver, gold, platinum, palladium, copper, zinc, iron, and carbon. Apart from the biomedical applications of metallic NMs, including antimicrobial, anticancer, diagnostic, drug delivery, tissue engineering, and regenerative medicine applications, their environmental remediation potential is also discussed. Furthermore, safety concerns and safety regulations pertaining to green NMs are also discussed. Abstract : This review describes plant extract‐based synthesis of metallic nanomaterials (NMs), their applications, safety concerns, and regulations for NMs. Various metallic NMs are produced with the aid of sustainable and biocompatible plant extracts. Such green NMs are widely applicable to biomedical and environmental purposes. Also surveyed are safety assessments of green NMs by regulatory agencies in influential countries.